A bio-inspired optical system with a polymer membrane and integrated structure. (23rd November 2016) - Liang, Dan; Wang, Xuan-Yin
Abstract: A bio-inspired optical imaging system with a polymer membrane and integrated structure is proposed. Similar to the human eye, the presented system has a biomimetic multilayered optical structure and utilizes a solid–liquid mixed tunable lens as the variable-focus unit. The focal length of the imaging system can be adjusted flexibly through the deformation of the tunable lens when it is compressed. A detailed description of the design principle, materials and fabrication process of the system is presented. The deformation property, adjustable range and surface roughness of the tunable lens are measured. Images under different displacement loads are captured, and the relationships among the back focal length (BFL) and effective focal length (EFL) of the system and the change in radius of the tunable lens are analyzed. A 7.6 times variation of the BFL is achieved through a tiny alteration in radius of 1.2 mm. All the measured resolutions during the deformation stage are larger than 40 line pairs mm −1, and the imaging system shows good optical quality and stability. The proposed optical system is of interest for the development of compact and stable imaging systems with a large zooming range.